OPTIMAL QUANTITY ALLOCATION DECISION IN REVENUE SHARING CONTRACT - Shafiq, Muhammad; Luong, Huynh Trung (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
This paper is focused on facilitating the manufacturer in making quantity allocation decisions. A revenue-sharing model with prior commitment from the retailers, two-way penalties, and reallocation of pre-allocated quantities is proposed to coordinate a supply chain comprising one manufacturer and two retailers facing stochastic demand. Over and under-purchase penalties are introduced to motivate the retailers to commit close to expected demand. In contrast, the under-supply penalty is presented for the manufacturer to compensate the stock-out loss of the retailers. Reallocation of pre-allocated quantities is also allowed to reduce the allocation risk of the manufacturer. The analysis reveals that the proposed model helps motivate stakeholders to share accurate demand information through a reward-penalty mechanism. Moreover, coordination improves the performance of the supply chain with a “win-win” solution for the stakeholders. The case study results reveal that the proposed model through the reward-penalty mechanism ensures true information sharing. Furthermore, reallocation reduces the possibility of waste. This is the first revenue-sharing model, including prior commitments, two-way penalties, and reallocation of pre-allocated quantities.